TABULAR INTEGRATION IN COMPUTING INDEFINITE INTEGRALS - Abdurashidov, Nuriddin; Eshtemirov , Eshtemir; Rustamov , Bilol; Normanova , Charos (Scientific practical conference, 2026)
This article is devoted to a comparative analysis of the effectiveness of algorithmic methods in computing indefinite integrals, in comparison with traditional recursive formulas. It also aims to provide a scientific justification of the mathematical foundations of tabular integration and its systematic algorithms used in the computational process.